Norditerpenoids and diterpenoids from Salvia multicaulis with antituberculous activity - (:unkn) unknown (AMER CHEMICAL SOC, 1997)
From the roots of Salvia multicaulis, four new aromatic norditerpenoids, multicaulin (1), 12-demethylmulticauline (2), multiorthoquinone (3), and 12-demethylmultiorthoquinone (4), two new abietane diterpenoids, 12-methyl-5-dehydrohorminone (5) and 12-methyl-5-dehydroacetylhorminone (6), as well as a new pimarane diterpenoid, salvipimarone (7), were isolated. Also obtained in this investigation were the known compounds alpha-amyrin, hinokione, horminone, lupeol, manool, 1-oxoferruginol, 18-oxoferruginol, pisiferal, and sempervirol. The structures of compounds 1-7 were established by 1D and 2D NMR techniques and by chemical methods. The antituberculous activity of 1-7 was tested against Mycobacterium tuberculosis strain H37Rv, and all compounds were found to be significantly active, with 2 and 4-6 being the most potent substances. Six of these novel compounds were evaluated against a number of additional bacterial cultures.
Keywords: ABIETANE DITERPENES; MILTIORRHIZA; PRIONITIS